Analyse des homonymes français dans la poésie de Maurice Carême - Ade Fitria Waljannah; Rabiah Adawi (Universitas Negeri Semarang, 2026)
Homonyms are defined as words with the same signifier, but different meanings. This research aims to analyze the types of homonymies in Maurice Carême’s poetry and determine which type is most frequent. The research focuses on the types of homonyms used in nineteen poems. This research uses a qualitative descriptive method, with primary data drawn from the poems in Maurice Carême’s book. According to the classification of Guechi and Saadani (2021), homonyms are divided into three types: heterographic homophones, homographic homophones, and heterophonic homographs. The analysis of 19 poems revealed 58 homonymous data, with the following details: 25 heterographic homophones (43.103%), 18 homographic homophones (31.034%), and 15 heterophonic homographs (25.862%). These results show that heterograph homophones are the most common type used by Maurice Carême. The use of homonyms in Carême’s poems demonstrates the richness of the language and creates plays on meaning that reinforce the poems’ aesthetic effect. This research also highlights the challenges French language learners face in understanding the meanings of homonyms in context.